Effect of Chalara longipes on decomposition of humic acids from Picea abies needle litter - Koukol, O; Gryndler, M; Novák, F; Vosátka, M (Folia microbiologica, 2004)
The effect of the saprotrophic ascomycete Chalara longipes on the decomposition of humic acids was determined in a cultivation experiment. The fungus was incubated in liquid cultures in a full-strength (F system) and an organic nitrogen-free medium (F-N system), both amended with pure humic acids isolated from spruce forest litter. Fungal biomass production was highest in the F system with humic acids and lowest in the F-N system, the effect of organic nitrogen and humic acids being significant (p < 0.05). The presence of organic nitrogen seems to be essential for growth. The fungus utilized humic acids; molar mass distribution in media obtained by gel-permeation chromatography showed decrease in the humic acids fraction. Decolorization of the media reached 75 and 64 % in the F and F-N systems, respectively. The molar mass of humic acids probably also decreased as estimated from the increase in the absorbance A465/A665 (A4/A6) ratio. It is assumed that the utilization of humic acids may be mediated by the production of organic acids (as their components) and production of some oxidative enzymes.
Keywords: smrk; půdní mikrobiologie; Ecosystem; Humic Substances; Ascomycota; molekulová hmotnost; Molecular Weight; Picea; Biomass; biomasa; Soil Microbiology; ekosystém; biodegradace; huminové látky; Biodegradation, Environmental